2011
DOI: 10.1016/j.biomaterials.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment induced spheroid to sheeting transition of immortalized human keratinocytes (HaCaT) cultured in microbubbles formed in polydimethylsiloxane

Abstract: The in vivo cellular microenvironment is regulated by a complex interplay of soluble factors and signaling molecules secreted by cells and it plays a critical role in the growth and development of normal and diseased tissues. In vitro systems that can recapitulate the microenvironment at the cellular level are needed to investigate the influence of autocrine signaling and extracellular matrix effects on tissue homeostasis, regeneration, and disease development and progression. In this study we report the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…We showed that arrays of spherical cavities formed on PDMS [7] using this technique can be used for culturing cancer cells as spheroids [8]. The unique geometry of microbubbles allows the cells to rapidly condition their microenvironment by secreting soluble factors to influence their function [9]. Also, perfusion culture system using microbubble arrays has shown that Colo205 cells cultured as spheroids under flow are more resistant to doxorubicin treatment resembling the actual disease condition [10].…”
Section: Editorialmentioning
confidence: 99%
“…We showed that arrays of spherical cavities formed on PDMS [7] using this technique can be used for culturing cancer cells as spheroids [8]. The unique geometry of microbubbles allows the cells to rapidly condition their microenvironment by secreting soluble factors to influence their function [9]. Also, perfusion culture system using microbubble arrays has shown that Colo205 cells cultured as spheroids under flow are more resistant to doxorubicin treatment resembling the actual disease condition [10].…”
Section: Editorialmentioning
confidence: 99%
“…Recently, we introduced microbubble (MB) well array technology and demonstrated its use to sustain single and small cell cultures for extended periods of time (>10 days) (Giang et al 2008; Chandrasekaran et al 2011). Microbubbles are spherical cavities formed in polydimethylsiloxane (PDMS) using the gas expansion molding (GEM) process (Giang et al 2007, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of enrichment of TGF-beta for sheeting behaviour was shown in a study comparing standard spheroid versus microbubble 3D cultures of keratinocytes [16]. While in the first, secreted molecules such as TGF-beta could diffuse freely, the compartmentation induced by the microbubble cultivation technique arguably led to a local increase in TGF-beta which induced a sheeting cell growth [16]. Using a similar chip-based technology featuring micro-fenestrated 300-m wide compartments (KIT Chip), we could recently confirm these findings and show a regular layered expression of keratinocyte differentiation markers, KRT14 and KRT10 (Fig.…”
mentioning
confidence: 98%
“…Close to definitive wound healing, fibroblasts release TGF-beta, which shifts keratinocytes to the basal phenotype, i.e. suppressing hyperproliferation, activating the standard keratinocyte differentiation program, stimulating the production of ECM components, and inducing normal keratinocyte layering [6,16]. The critical role of enrichment of TGF-beta for sheeting behaviour was shown in a study comparing standard spheroid versus microbubble 3D cultures of keratinocytes [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation